2022
DOI: 10.1186/s12889-022-14377-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between myopia and near work, time outdoors and socioeconomic status in children and adolescents

Abstract: Background To investigate environmental and social risk factors for myopia in children and adolescents in Germany. Methods 1437 children aged between 3 and 18 inclusive were examined as part of the LIFE Child study based in Leipzig, Germany. Information about leisure time activities and social status was ascertained by parents and children in a questionnaire. Refractive status was attained by measuring noncycloplegic autorefraction. Myopia was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The authors proposed that economic development fosters a desire for wealth, leading to increased educational pursuit and heavier academic burdens, ultimately resulting in higher myopia rates [ 266 ]. While other studies found higher socioeconomic status to be associated with myopia [ 264 , 265 , 267 , 268 ], some failed to find any such association [ 61 , 187 , 269 ]. The conflicting evidence on socioeconomic status and myopia may stem from variations in the definition and classification of socioeconomic status, as well as unmeasurable factors like parental involvement and academic pressure.…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…The authors proposed that economic development fosters a desire for wealth, leading to increased educational pursuit and heavier academic burdens, ultimately resulting in higher myopia rates [ 266 ]. While other studies found higher socioeconomic status to be associated with myopia [ 264 , 265 , 267 , 268 ], some failed to find any such association [ 61 , 187 , 269 ]. The conflicting evidence on socioeconomic status and myopia may stem from variations in the definition and classification of socioeconomic status, as well as unmeasurable factors like parental involvement and academic pressure.…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“… Pärssinen & Kauppinen (2022) have found an association between close work time and incidence of myopia in a historical survey of around 5000 Finnish children. An association between longer near work sessions and incidence of myopia has been also been recently found in around 1400 children aged between three and 18 years old ( Philipp et al, 2022 ). Close work is associated with the fovea and perifovea experiencing accommodative lag, not the peripheral retina, which has mostly accommodative lead during close work ( Flitcroft, 2012 ).…”
Section: Discussionmentioning
confidence: 76%
“…However, since this correlation contradicts the assumption that more outdoor time tends to prevent myopia or myopic progression, 60 it should be questioned critically. This is emphasised by the fact that in our LIFE cohort of children, those who were outdoors more frequently during the week were also less myopic 61 …”
Section: Discussionmentioning
confidence: 84%
“…This is emphasised by the fact that in our LIFE cohort of children, those who were outdoors more frequently during the week were also less myopic. 61…”
Section: Media Use and Outdoor Timementioning
confidence: 99%